Factors related to functional exercise capacity amongst people with HIV in Durban, South Africa - Penelope M. Orton; Dudu G. Sokhela; Kathleen M. Nokes; Joseph D. Perazzo; Allison R. Webel (AOSIS, 2021)
Background: People with HIV (PWH), who engage in regular physical activity, have improved fitness, muscular strength, body composition, health-related quality of life and mental health symptoms, but PWH have amongst the lowest physical activity levels of those with any chronic health condition. Furthermore, there is scant evidence examining these relationships in PWH in Africa. Aim: To address these critical gaps, this cross-sectional descriptive research study examined the relationships between demographic, HIV-related, anthropometric factors, neighbourhood walkability and physical activity, amongst PWH in Durban, South Africa. Setting: Respondents (N = 100) were receiving primary healthcare in six eThekwini nurse-run municipal clinics. Methods: Self-reported socio-demographic data were collected, and HIV-related medical data were extracted from respondent's medical charts. Height and weight were measured to calculate the body mass index (BMI, kg/m2); neighbourhood walkability was measured on the Neighbourhood Environment scale; and physical activity, specifically functional exercise capacity, was measured by the 6-min walk test (6MWT). Results: On average, respondents were black African, female, approximately 38 years old and unemployed; men were of normal weight whilst women were overweight. Only 65% of the respondents reached the age- and sex-predicted distance during the 6MWT. Correlational analyses did not reveal any significant relationships between the functional exercise capacity and socio-demographic, HIV-related factors or anthropometric measures. Conclusion: South African PWH do not reach their predicated walking distance on the 6MWT. Engaging community agencies to promote walking as both a means of transportation and leisure physical activity may decrease the risks of a sedentary lifestyle and improve progression towards recommended physical activity targets.